EFFECTS OF ROOTSTOCK-SCION COMBINATIONS ON MACROELEMENTS AVAILABILITY OF THE VINES - Anna CSIKÁSZ-KRIZSICS; Lajos DIÓFÁSI (Journal of Central European Agriculture, 2009)
This study investigates macroelement contents (N, P, K, Ca, Mg) and their quality relations of 4 scion grape varieties (Italian Riesling, White Riesling, Chardonnay, Cabernet sauvignon) on 6 rootstock varieties (5C, 5BB, 125AA, 140Ru, 110R, Fercal) between 2001 and 2005. A field experiment was set up at Szentmiklós Hill (on the border of the town of Pécs) in southern part of Hungary in 1999. The investigated rootstocks had no statistically proven effect on the nitrogen levels of the leaves, but the scion varieties had. Phosphorus content of the leaves on rootstocks with Berlandieri x Riparia genetic background (5C, 5BB, 125AA) was lower at blooming than that on other investigated rootstocks. We found statistically significant differences in the calcium and magnesium content of leaves regarding rootstock and scion varieties too.